Performance evaluation of a twin-shaft gas turbine engine in mechanical drive service - Tahan, M. (Korean Society of Mechanical Engineers, 2017)
This study aimed at quantifying the effect of mechanical load on the performance of an 18.7 MW offshore gas turbine engine. The targeted engine is of two-shaft free power turbine configuration that operates as a mechanical driver for a process compressor in the gas compression service. The study is a part of a comprehensive performance health monitoring program to address the diagnostic and prognostic requirements in oil and gas offshore platforms and is motivated by the need to provide in-depth knowledge of the gas turbine engine performance. In this work, only the context of some design point key performance parameters and a limited set of collected operational data from the gas turbine in the real plant are available. Therefore, three major tasks, namely design point calculation, characteristic map tuning and off-design performance adaption, were needed to be performed. In order to check the validity of the proposed model, the obtained simulation results were compared with the operational data. The results indicate the maximum inaccuracy of the proposed model is 3.04 . Finally, by employing the developed model, the engine capability for power generation when exposed to various load speeds is investigated. The obtained result demonstrates at the maximum gas generator speed, every 3 decrease in mechanical speed leads to 1 decline in the gas turbine power output. Moreover, when the gas turbine operates under design power load and mechanical speed is lower than 80 of design speed, every 1 decrease in load speed results in 0.2 loss in thermal efficiency. The established relationship will assist proper assessment of mechanical drive gas turbines for performance health monitoring. © 2017, The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.